Paciente masculino de 56 años de edad que presenta retinopatía diabética con edema macular. - Moreno Bazán, Yuleidy Narcisa (2021)
Diabetes is the silent enemy that is affecting many people today, recent studies indicate that in developed countries it affects more than 10% of the population. Diabetes is the cause of the development of retinopathy, diabetic retinopathy is the 3rd leading cause of blindness in the world. Affecting people belonging to the EAP (economically active population), this generates large economic losses. As such, it is essential to detect it early in order to take the necessary actions to alleviate its effects. Diabetic retinopathy is irreversible and does not affect vision until it is advanced. It is necessary to instill in patients eye care, that they follow its controls and comply with the recommendations in order to protect their visual health.